Composition design of PLA/TPU emulsion blends compatibilized with multifunctional epoxy‐based chain extender to tackle high impact resistant ductile structures. Issue 12 (28th October 2021) - Kahraman, Yusuf; Alkan Goksu, Yonca; Özdemir, Burcu; Eker Gümüş, Beril; Nofar, Mohammadreza
Abstract: In this study, the composition of polylactide (PLA)/thermoplastic polyurethane (TPU) emulsion blends compatibilized with multifunctional epoxy‐based Joncryl chain extender was regulated to tackle high impact resistant structures with improved ductility. PLA/TPU blends at different blending ratios of 95wt/05wt, 85wt/15wt, 75wt/25wt, and 65wt/35wt were first melt blended with 0.5 wt% of Joncryl. In all compositions, although the TPU droplets were significantly refined with the addition of Joncryl, the impact strength and ductility of the blends increased dramatically only at 75wt/25wt and 65wt/35wt blending ratios. The 75wt/25wt blend was then melt blended with various Joncryl contents of 0.25, 0.5, 0.75, and 1.0 wt%. It was illustrated that 0.5 wt% Joncryl was high enough to reach a blend with the highest impact strength and ductility of around 110 kJ/m 2 and 150%, respectively. This was while the tensile strength and modulus values remained comparable with those of neat PLA. The rheological experiments and the dynamic mechanical analysis confirmed that the complex viscosity and the storage modulus of the compatibilized blends were improved as a result of increased melt strength of PLA and the interfacial compatibilization through using Joncryl. Abstract :